EDUKASI PEMBUATAN MASKER ORGANIK DARI BAHAN DASAR KOMBINASI BERAS DAN DAUN RICA DI DESA MAKU, KABUPATEN SIGI, SULAWESI TENGAH - Anggi, Viany; Sujati, Ni Wayan; Rakanita, Yasinta (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2023)
Community service activities are an important activity in the Higher Education Tridarma which must be carried out for independent and professional community empowerment from community powerlessness which is a global problem today. Pelita Mas Palu College of Pharmacy has a family medicinal plant garden in the area of ​​Maku Village, Dolo District, Sigi Regency, Central Sulawesi. For this reason, as a source of family medicinal plants in the area, so they were chosen for community service activities. This activity aims to provide knowledge to the people of Maku village about making organic masks from the basic ingredients of a combination of rice and rica leaf ingredients which function as antioxidants in regenerating skin cells. The expected outputs from this activity are cultivating an entrepreneurial spirit in the products produced, providing counseling, establishing a family medicinal plant garden, providing free medical check-ups for the people of Maku village and providing free groceries. The method used in this activity was forming hamlet groups according to the order of hamlets in Maku village, delivering material to be delivered, where 30% of participants did not understand organic mask making, delivering material for 1 hour followed by planting TOGA, free health checks and free groceries. The results of the activity show that the people in Maku village are able to understand educational materials for making organic masks with an understanding level of 70%